HYPOCRISY AS SEEN TRHOUGH METAPHOR IN ANNE SEXTONâ€™S â€œGHOSTSâ€ - Tesa Lonika Barli Putri; Rr. Arielia Yustisiana (Universitas Katolik Widya Mandala Surabaya, 2017)
This research analyzes literary work which focused on a poem. This research aimed to describe the Â metaphor dealing with hypocrisy in the poem entitled â€œGhostsâ€ written by Anne Sexton. The research focused on two major purposes: first, to describe the lines which belonged to metaphor dealing with hypocrisy and second, to reveal the theme of bitterness in the poem. Moreover, there were some theories which were used in this Â research. They were theory of meaning, figure of speech, metaphor, theme, and bitterness. Furthermore, this research had two approaches, that is, structural and formalist approach. The method used in analyzing the data in this research is descriptive â€“qualitative method. The technique of collecting data in this research was library Â research. The analysis showed that: there are three hypocrisies which are seen through metaphor in the poem, hypocrisy related to women, men, and children. Moreover, the three metaphors constituted the same theme of the whole poem, that is, bitterness . Â Â Keywords: Metaphor, Hypocrisy, Theme, Bitterness